Differential Role of Sex and Age in the Synaptic Transmission of Degus (Octodon degus) - Oliva, Carolina A.; Rivera, Daniela S.; Mariqueo, Trinidad A.; Bozinovic, Francisco; Inestrosa, Nibaldo C. (Frontiers in Integrative Neuroscience, 2022)
Octodon degus is a diurnal, long-lived social animal widely used to perform longitudinal studies and complex cognitive tasks to test for physiological conditions with similitude in human behavior. They show a complex social organization feasible to be studied under different conditions and ages. Several aspects in degus physiology demonstrated that these animals are susceptible to environmental conditions such as stress, fear, feeding quality, isolation. However, the relevance of these factors in this animal's life depends on sex and age. Despite its significance, few studies intent to characterize neurological parameters that include these two parameters. To determine the basal neurophysiological status, we analyzed basic electrophysiological parameters generated during basal activity or synaptic plasticity in brain slices of young and aged females and males degus. We studied the hippocampal circuit of animals kept in social ambient in captivity under controlled conditions. The study of basal synaptic activity in young animals (12-24 months old) was similar between sexes, but females showed more efficient synaptic transmission than males. We found the opposite in aged animals (60-84 months old), where males had a more efficient basal transmission and facilitation index than females. Furthermore, females and males develop significant but not different long-term synaptic plasticity (LTP). However, aged females need to recruit twice as many axons to evoke the postsynaptic activity same as males, and four times more when compared to young females. These data suggest that, unlike males, the neural status of aged females changes showing less number or functional axons available at advanced ages. Our data represents the first approach to incorporate the effect of sex along with age progression in basal neural status.